Cover Feature: Peptide‐Mimicking Poly(2‐oxazoline)s Displaying Potent Antimicrobial Properties (2/2021). (22nd January 2021) - Zhou, Min; Jiang, Weinan; Xie, Jiayang; Zhang, Wenjing; Ji, Zhemin; Zou, Jingcheng; Cong, Zihao; Xiao, Ximian; Gu, Jiawei; Liu, Runhui
Abstract : The Cover Feature shows that poly(2‐oxazoline)s were demonstrated to be a new class of functional peptide mimics to display potent antimicrobial activity in vitro and in vivo against methicillin‐resistant Staphylococcus aureus (MRSA), while alleviating antibiotic resistance with their antimicrobial mechanism and killing kinetics, which were tunable by varying the poly(2‐oxazoline)s' sidechain structures. More information can be found in the Concept by Runhui Liu et al. . Cover picture design by Zhemin Ji.